(untitled) (Economic studies journal, 2019)
The purpose of the study was to highlight the impact of organizational culture on enhancing knowledge sharing at TAHRI Mohamed University. The study used the experimental method by addressing the theoretical rooting of organizational culture and knowledge sharing, reviewing previous studies, using the SPSS and AMOS program, a sample of 172 members of the study population of 764 faculty members belonging to the eight faculties of the university were analyzed. the study conclute several results, the most important of which is that organizational culture accounts for 68% of knowledge sharing, and the growing organizational culture of 1% promotes knowledge sharing by 0.82%, which calls on the administration of TAHRI Mohamed University to work on developing team spirit among faculty members. Knowledge sharing.